Desain Sistem Informasi Monitoring Berbasis Website Untuk Menilai Perkembangan Siswa - Dewi Mardhiyana (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
One of the objectives of the assessment is monitoring, which aims to see whether the implementation of the learning assessment has been in accordance with the assessment plan or not. In the era of the industrial revolution 4.0, technology is needed to facilitate the assessment process so that it can be carried out by various parties. The busyness of parents is one factor in the need for a tool to monitor the development of children at school. This study aims to produce a website-based monitoring information system design in assessing student development. The method used is a research and development method, with a 4-D model, namely definition, design, development, and dissemination. This article only discusses two stages, namely the definition stage and the design stage. At the definition stage, some information was collected regarding problems in monitoring student assessments. Data was collected using a questionnaire method given to high school students and teachers, as well as interviews with several parents of high school students. The results of the definition stage indicate that a student development monitoring system is needed that can be accessed by parents from home. At the design stage, a website-based monitoring information system design is designed that contains seven main views, namely: Login, Home, Student Identity, Grade List, Monitoring, Settings, and Logout. Keywords: Assisted information system, monitoring, website, student learning outcomes